Wave propagation in equivalent continuums representing truss lattice materials. (November 2015) - Messner, Mark C.; Barham, Matthew I.; Kumar, Mukul; Barton, Nathan R.
Highlights: Develops an equivalent continuum model for stretch-dominated lattice materials. Verifies model against the dispersion spectrum predicted by the Bloch wave theory. Correct long wavelength dynamics requires consideration of microinertial effects. Abstract: Stiffness scales linearly with density in stretch-dominated lattice meta-materials offering the possibility of very light yet very stiff structures. Current additive manufacturing techniques can assemble structures from lattice materials, but the design of such structures will require accurate, efficient simulation methods. Equivalent continuum models have several advantages over discrete truss models of stretch dominated lattices, including computational efficiency and ease of model construction. However, the development an equivalent model suitable for representing the dynamic response of a periodic truss in the small deformation regime is complicated by microinertial effects. This paper derives a dynamic equivalent continuum model for periodic truss structures suitable for representing long-wavelength wave propagation and verifies it against the full Bloch wave theory and detailed finite element simulations. The model must incorporate microinertial effects to accurately reproduce long wavelength characteristics of the response such as anisotropic elastic soundspeeds. The formulation presented here also improves upon previous work by preserving equilibrium at truss joints for simple lattices and by improving numerical stability by eliminating vertices in the effective yield surface.